Generasi Muslim Milenial Sebagai Model Islam Wasaṭiyyah Zaman Now - Musyafangah Musyafangah; Bekti Taufiq Ari Nugroho; Wildan Nur Hidayat (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2019)
This study study describes and analyzes the notion of wasaṭiyyah Islam, which explains the millennial generation of wasaṭiyyah Islam. Islamic wasaṭiyyah must be taken from the clerical explanation, so as not to trigger 'missunderstanding' and intolerant attitude that damages the image of Islam itself. This research belongs to library research. Data collection is done by quoting, adapting, and analyzing the representative literaries and relevant to the issues discussed, then reviewing and concluding them. The results of this study indicate that: 1) Through the process of literacy and teaching the true religion, millennial generations can be agents of change in syiar Islam wasaṭiyyah. Tolerant Islam, respect for diversity and a benevolent Islam for all people; 2) The nature, existence and urgency of Islam wasaṭiyyah is the generation of Islam ummatan wasatan interpreted as followers of religion that take the middle way or adherents of the principle of moderate, be a fair and balanced people in various things, both in terms of sharia and muamalah and can create harmony in life, because it can touch all aspects faced by humans, and offer the principles of unity by referring to the Qur'an as an open book, promoting justice, equality, tolerance, humanity, liberation and non-discrimination; 3) Phenomenology should not create a contradiction between a true and an incorrect religion. In a forced state, phenomenology can vigilantly distinguish pure and impure religiosity. There are two main perspectives of sociology that are often used as a basis in viewing religious phenomena in society, namely: functionalist perspective, and symbolic interactionism.